SMART LAMP BEBRBASIC ARDUINO UNO USING AN ANDROID SMARTPHONE - Fajar Muhammad; Andhika Rifqy, Dimas Fadli Devani, Paduloh (CV. ADIBA AISHA AMIRA, 2024)
In the rapidly developing digital era, the Internet of Things (IoT) and the popularity of smartphone control applications have opened the door to innovation in the development of automation and device control systems. This research project aims to design and develop a smart lamp that can be operated using an Arduino-based smartphone device. The combination of advances in IoT and rapidly growing demand for remote control solutions makes this project relevant and interesting. These smart lights will allow users to control their home lighting via a smartphone app, creating great flexibility and potential energy savings. In addition, this project will enable the development of skills in the fields of programming, electronics, and design, as well as contributing to the open-source community by sharing the design and source code of this project. This project will outline the development of smart lighting that focuses on energy efficiency and stronger integration with smartphone technology, which has potential impact in daily life and applications in various industrial sectors.